(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Knowing a person’s blood type is very important to know for medical purposes. Blood type is important to know, for the sake of transfusion, the right donor and identification in forensic medical cases such as identification in some criminal cases. Blood stains have an important role in revealing various legal and criminal cases. In the process of identifying bloodstains as evidence, the first thing that must be done is to determine whether the bloodstains actually contain blood molecules so that the blood group can then be identified. Blood group identification is generally done based on the ABO blood grouping system. There have been many criminal cases that have been revealed through the ABO blood group identification system. Blood type examination is one of the methods used when a crime case occurs in the community. There are 4 human blood groups (A, B, AB, and O) which are grouped based on the presence or absence of antigens on the surface of erythrocytes. Identification of blood group ABO system on fresh blood samples is easier to do than dried blood samples. This is because the cells in the dried blood are damaged. However, it is still possible to identify the blood group of dry blood samples. This is because the antigens on the surface of red blood cells remain intact even though the cells have been destroyed. The method commonly used to identify the blood group of dry blood samples is the elution absorption method. This method is a very sensitive method and can detect the presence of antigens indirectly.